Counting the World's Poor : Problems and Possible Solutions - Deaton, Angus (Washington, DC: World Bank, 2014)
As recent discussions have made clear, the apparent lack of poverty reduction in the face of historically high rates of economic growth-both in the world as a whole and in specific countries (most notably India)-provides fuel for the argument that economic growth does little to reduce poverty. How confident can we be that the data actually support these inferences? At the international level, the regular revision of purchasing power parity exchange rates plays havoc with the poverty estimates, changing them in ways that have little or nothing to do with the actual experience of the poor. At the domestic level, the problems in measuring poverty are important not only for the world count but also for tracking income poverty within individual countries. Yet, in many countries, there are large and growing discrepancies between the survey data-the source of poverty counts-and the national accounts-the source of the measure of economic growth. Thus economic growth, as measured, has at best a weak relationship with poverty, as measured.